Deciphering the key pathway for triterpenoid biosynthesis in Azadirachta indica A. Juss.: a comprehensive review of omics studies in nature’s pharmacy - Dave, Nitish; Iqbal, Atif; Patel, Margi; Kant, Tarun; Yadav, Virendra Kumar; Sahoo, Dipak Kumar; Patel, Ashish (Frontiers in Plant Science, 2023)
Since ancient times, Azadirachta indica, or Neem, has been a well-known species of plant that produces a broad range of bioactive terpenoid chemicals that are involved in a variety of biological functions. Understanding the molecular mechanisms that are responsible for the biosynthesis and control of terpenoid synthesis is majorly dependent on successfully identifying the genes that are involved in their production. This review provides an overview of the recent developments concerning the identification of genes in A. indica that are responsible for the production of terpenoids. Numerous candidate genes encoding enzymes that are involved in the terpenoid biosynthesis pathway have been found through the use of transcriptomic and genomic techniques. These candidate genes include those that are responsible for the precursor synthesis, cyclization, and modification of terpenoid molecules. In addition, cutting-edge omics technologies, such as metabolomics and proteomics, have helped to shed light on the intricate regulatory networks that govern terpenoid biosynthesis. These networks are responsible for the production of terpenoids. The identification and characterization of genes involved in terpenoid biosynthesis in A. indica presents potential opportunities for genetic engineering and metabolic engineering strategies targeted at boosting terpenoid production as well as discovering novel bioactive chemicals.